Comparison of laparoscopy-assisted and open radical gastrectomy for advanced gastric cancer: A retrospective study in a single minimally invasive surgery center. Issue 25 (June 2016) - Hao, Yingxue; Yu, Peiwu; Qian, Feng; Zhao, Yongliang; Shi, Yan; Tang, Bo; Zeng, Dongzhu; Zhang, Chao
Abstract : Abstract: Laparoscopy-assisted gastrectomy (LAG) has gained international acceptance for the treatment of early gastric cancer (EGC). However, the use of laparoscopic surgery in the management of advanced gastric cancer (AGC) has not attained widespread acceptance. This retrospective large-scale patient study in a single center for minimally invasive surgery assessed the feasibility and safety of LAG for T2 and T3 stage AGC. A total of 628 patients underwent LAG and 579 patients underwent open gastrectomy (OG) from Jan 2004 to Dec 2011. All cases underwent radical lymph node (LN) dissection from D1 to D2+. This study compared short- and long-term results between the 2 groups after stratifying by pTNM stages, including the mean operation time, volume of blood loss, number of harvested LNs, average days of postoperative hospital stay, mean gastrointestinal function recovery time, intra- and post-operative complications, recurrence rate, recurrence site, and 5-year survival curve. Thirty-five patients (5.57%) converted to open procedures in the LAG group. There were no significant differences in retrieved LN number (30.4 ± 13.4 vs 28.1 ± 17.2, P = 0.43), proximal resection margin (PRM) (6.15 ± 1.63 vs 6.09 ± 1.91, P = 0.56), or distal resection margin (DRM) (5.46 ± 1.74 vs 5.40 ± 1.95, P = 0.57) between the LAG and OG groups, respectively. The mean volume of blood loss (154.5 ± 102.6 vs 311.2 ± 118.9 mL, P < 0.001), mean postoperative hospital stay (7.6 ± 2.5 vs 10.7 ± 3.6 days, P < 0.001), mean time for gastrointestinal function recovery (3.3 ± 1.4 vs 3.9 ± 1.5 days, P < 0.001), and postoperative complications rate (6.4% vs 10.5%, P = 0.01) were clearly lower in the LAG group compared to the OG group. However, the recurrence pattern and site were not different between the 2 groups, even they were stratified by the TNM stage. The 5-year overall survival (OS) rates were 85.38%, 79.70%, 57.81%, 34.60% and 88.31%, 75.49%, 56.84%, 33.08% in patients with stage Ib, IIa, IIb, and IIIa, respectively, in the LAG and OG groups. There were no statistically significant differences in the OS rate for patients with the same TNM stage between the 2 groups. LAG with radical LN dissection is a safe and technically feasible procedure for the treatment of AGC staged below T3.